Alginate coated mesoporous silica nanoparticles as oral delivery carrier of curcumin and quercetin to colon cancer: preparation, optimization, characterization, and anticancer activity - Alallam, Batoul; Abdkadir, Erazuliana; Hayati, Alfiah; Keong, Yong Yoke; Lim, Vuanghao (Springer, 2025)
The synergistic bioactive effect of polyphenols can enhance the development of functional foods to prevent chronic diseases such as cancer. Curcumin and quercetin have been shown to possess anticancer properties. The combination of curcumin and quercetin has been shown to provide synergistic effects against cancer cell proliferation. The prospect of exhibiting a synergistic antitumor effect is to target a multi-pathway approach, reduce dosage, and minimize potential side effects. However, their effectiveness is limited by poor bioavailability. Nanoscale delivery systems are promising strategies for the delivery of polyphenols. Nevertheless, many of these nanomaterials are yet to be commercialized owing to their lack of versatility or manufacturing costs. Thus, developing a formulation that responds to body conditions is a great challenge and would provide a better way to orally administer polyphenols. Therefore, this study aimed to develop a dual-responsive disulfide-linked core–shell nanohybrid for oral delivery and targeted release of polyphenols in the colon. The nanohybrid had monodispersed structures with a size of < 50 nm, large pore size (> 9.5 nm), surface area of > 700 m2/g, and zeta potential of − 30.71 ± 0.71 mV. The polyphenols were encapsulated into the nanohybrid in their amorphous state, with a loading capacity of 20.49%. The coating enhanced the release of polyphenols into the intestinal fluid, potentially improving their delivery to the colon. The nanohybrid demonstrated a better anticancer effect than the free polyphenols against HT29 cancer cells. This study explores the use of a dual-sensitive alginate-coated mesoporous silica nanohybrid as a carrier for the enhanced delivery of polyphenols.